2013
DOI: 10.1177/0960327113512342
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative stress on cardiotoxicity after treatment with single and multiple doses of doxorubicin

Abstract: The mechanism of doxorubicin (DOX)-induced cardiotoxicity remains controversial. Wistar rats ( n = 66) received DOX injections intraperitoneally and were randomly assigned to 2 experimental protocols: (1) rats were killed before (−24 h, n = 8) and 24 h after (+24 h, n = 8) a single dose of DOX (4 mg/kg body weight) to determine the DOX acute effect and (2) rats ( n = 58) received 4 injections of DOX (4 mg/kg body weight/week) and were killed before the first injection (M0) and 1 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0
5

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 51 publications
1
20
0
5
Order By: Relevance
“…Several mechanisms have been postulated to explain sexual dimorphism of chronic DOX-induced cardiotoxicity including differences in myocardial energy metabolism, mast cell activation, and cardiolipin remodeling [11, 12, 14]. Since the mechanisms of acute DOX-induced cardiotoxicity may be different from those of chronic cardiotoxicity [17], it is important to investigate the mechanisms of sex-related differences in acute DOX-induced cardiotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Several mechanisms have been postulated to explain sexual dimorphism of chronic DOX-induced cardiotoxicity including differences in myocardial energy metabolism, mast cell activation, and cardiolipin remodeling [11, 12, 14]. Since the mechanisms of acute DOX-induced cardiotoxicity may be different from those of chronic cardiotoxicity [17], it is important to investigate the mechanisms of sex-related differences in acute DOX-induced cardiotoxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Some mechanisms are simultaneously involved in cardiotoxicity that is induced by doxorubicin, such as matrix metalloproteinases (MMP)-2 activation [4,6], and an increase in oxidative stress [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…however, with the increase in the dose of Adriamycin, its toxic side effects became more severe. The most severe side effect is cardiac injury (7,28). A previous study has found that administering Adriamycin to BALB/c nude mice transplanted with the leukemic cell line P388 causes cardiac injury, which is alleviated following co-treatment with Adriamycin and quercetin (12).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study has found that administering Adriamycin to BALB/c nude mice transplanted with the leukemic cell line P388 causes cardiac injury, which is alleviated following co-treatment with Adriamycin and quercetin (12). The mechanism underlying the cardiac toxicity of Adriamycin may be oxidative damage to cardiomyocytes, which is associated with various types of heart injury (24,28). SOD scavenges superoxide radicals in cells to protect them from damage.…”
Section: Discussionmentioning
confidence: 99%